PENGARUH KELENGKAPAN SARANA BELAJAR DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SD NEGERI KELAS V - Kurniasih, Novi Tri (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract : The Effect Learning Means Completeness and Learning Activity for Mathematic Learning Result of Fiveth Grade Students Elementary School in Klirong District. The purpose of this research are to prove (1) the effect of different learning means completeness for Mathematic learning result of fiveth grade students elementary school in Klirong District, Academic Year 2012/2013; (2) the effect of different learning activity for Mathematic learning result of fiveth grade students elementary school in Klirong District, Academic Year 2012/2013; (3) the effect of interaction between learning means completeness and learning activity for Mathematic learning result of fiveth grade students elementary school in Klirong District, Academic Year 2012/2013. This research is a quantitative research using expost facto method. Researcher used stratified random sampling as the sampling technique. Data collecting techniques are formative evaluation test of Mathematics result of learning and non-formative test in a form of questionnaire for learning means completeness and questionnaire for learning activity. Data analysis of this research is two-lane variant analysis (Anava 2x2). Prerequisite test analysis are normality test and homogeneity test. For further test after Anava, researcher using the Scheffe test. Keywords: learning means , learning activity, result learning, Mathematic Abstrak: Pengaruh Kelengkapan Sarana Belajar dan Aktivitas Belajar terhadap Hasil Belajar Matematika Siswa SD Negeri Kelas V. Tujuan penelitian ini adalah untuk membuktikan (1) ada tidaknya pengaruh perbedaan kelengkapan sarana belajar terhadap hasil belajar Matematika siswa SD N kelas V se-Kecamatan Klirong tahun ajaran 2012/2013; (2) ada tidaknya pengaruh perbedaan aktivitas belajar terhadap hasil belajar Matematika siswa SDN kelas V se-Kecamatan Klirong tahun ajaran 2012/2013; (3) ada tidaknya pengaruh interaksi kelengkapan sarana belajar dan aktivitas belajar terhadap terhadap hasil belajar Matematika siswa SDN kelas V. Penelitian ini merupakan penelitian kuantitatif dengan metode ekspost facto. Teknik sampling yang digunakan peneliti adalah stratified random sampling. Teknik pengumpulan data adalah teknik tes berupa soal hasil belajar Matematika dan teknik nontes berupa angket kelengkapan sarana belajar dan aktivitas belajar. Analisis data yang digunakan peneliti adalah Analisis Varian Dua Jalur (Anava 2x2). Uji prasyarat analisis menggunakan uji normalitas dan uji homogenitas. Uji lanjut pasca anava menggunakan uji Scheffe. Kata Kunci: sarana belajar, aktivitas belajar, hasil belajar, Matematika